SOSIALISASI POLA ASUH ANAK BERKEBUTUHAN KHUSUS DI YAYASAN RUMAH GADANG CEREBRAL PALSY SUMATERA BARAT - Siska Elasta Putri; Bustamin Bustamin; Muhammad Hizbi Islami (Menara Pengabdian, 2022)
Cerebral Palsy (CP) is a disorder that damages motor cells in the central nervous system due to brain abnormalities in a child. This causes children with cerebral palsy to require special treatment. The role of parents is very important in improving the quality of life of children with cerebral palsy. Therefore, there is a need for special socialization for parents regarding parenting issues. This service is carried out to assist parents to increase knowledge related to parenting patterns for children with cerebral palsy. The activity was carried out at the Rumah Gadang Cerebral Palsy Foundation, West Sumatra. The method used is to provide explanations and discussions.Keywords: Socialization, Children with Special Needs, Cerebral Palsy